PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH KELAS III SEKOLAH DASAR - Ni Luh Ayu Ratih; I Made Sujana Adnyana (STKIP Subang, 2026)
This study was motivated by the low mathematics learning outcomes of third grade elementary school students, particularly in addition and subtraction of whole numbers. The problem was related to limited student engagement and the use of less varied learning approaches in the classroom. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Make a Match learning model. The research used Classroom Action Research conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were third grade students. Data were collected through tests to measure learning outcomes and observations to capture student participation during the learning process. The data were analyzed using descriptive methods. The findings show that the implementation of the Make a Match learning model improves students’ mathematics learning outcomes, as reflected in higher average scores and increased learning completeness. In addition, students become more active and engaged during the learning process. Therefore, the Make a Match learning model is effective in improving students’ mathematics learning outcomes on addition and subtraction of whole numbers